2023
DOI: 10.3389/fimmu.2023.1127743
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota derived bile acid metabolites maintain the homeostasis of gut and systemic immunity

Abstract: Bile acids (BAs) as cholesterol-derived molecules play an essential role in some physiological processes such as nutrient absorption, glucose homeostasis and regulation of energy expenditure. They are synthesized in the liver as primary BAs such as cholic acid (CA), chenodeoxycholic acid (CDCA) and conjugated forms. A variety of secondary BAs such as deoxycholic acid (DCA) and lithocholic acid (LCA) and their derivatives is synthesized in the intestine through the involvement of various microorganisms. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 175 publications
(232 reference statements)
0
13
0
Order By: Relevance
“…Meanwhile, TCC exposure decreased the intestinal-conjugated BAs including TCA, TUDCA, T-αMCA, and T-βMCA. A previous study reported that an increased abundance of CA and a decreased abundance of DCA and LCA were found in the fecal tissues of IBD patients . These results suggested that TCC exposure markedly disrupted BA metabolism, thus exacerbating intestinal inflammation .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Meanwhile, TCC exposure decreased the intestinal-conjugated BAs including TCA, TUDCA, T-αMCA, and T-βMCA. A previous study reported that an increased abundance of CA and a decreased abundance of DCA and LCA were found in the fecal tissues of IBD patients . These results suggested that TCC exposure markedly disrupted BA metabolism, thus exacerbating intestinal inflammation .…”
Section: Discussionmentioning
confidence: 82%
“…A previous study reported that an increased abundance of CA and a decreased abundance of DCA and LCA were found in the fecal tissues of IBD patients. 35 These results suggested that TCC exposure markedly disrupted BA metabolism, thus exacerbating intestinal inflammation. 36 In addition, marked downregulation in the levels of indole metabolites such as IAA, IAM, ILA, IPA, and IAlD from gut microbes suggested that TCC exposure induced disruption of intestinal AhR-mediated gut barrier function, since most of them are endogenous ligands of AhR maintaining immune homeostasis.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the gut–liver axis plays a key role in regulating the enterohepatic circulation of bile acids, the size of bile acid pool, and the composition of bile acids, which control the overgrowth of intestinal bacteria that metabolize bile acids to regulate host metabolism. 19 TBA may reduce the risk of malnutrition after liver transplantation, which may be related to its protective effect on the liver and its interaction with the enterohepatic axis. 20 However, there is scant experimental evidence available at present, and further research is needed to verify this.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial-derived metabolites such as short chain fatty acids and tryptophan and bile acid metabolites, interact with various metabolite receptors expressed on enterocytes or enteroendocrine cells (EEC) to regulate gut homeostasis 64 . In addition, microbial-derived metabolites have widely effects on the immune cells such as macrophages 65 , 66 . Since neuron-macrophage interaction disorder may affect the homeostasis of the enteric nervous system (ENS), thereby leading to gastrointestinal dysfunction 67 , microbial-derived metabolites also affect the gut motility.…”
Section: Discussionmentioning
confidence: 99%